PENGARUH SOLVABILITAS, UKURAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN TERHADAP MANAJEMEN LABA - Nurul Fatikhah (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
Profit in financial reports can be used as a way to assess whether management is good or bad in managing company assets. Earnings management is viewed from two points of view. Academics see it as the right of company managers to set certain accounting policies, while practitioners consider it fraud. This research aims to determine how solvency (leverage), company size, and dividend policy influence earnings management. The results of this research took all manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2022 observation period. Quantitative methods were used in this study with purposive sampling as a sample selection technique, to test the hypothesis. This research produced data from 252 companies, with 63 companies as samples. This research shows that leverage affects earnings management, but company size does not affect earnings management. On the contrary, dividend policy seems to have a positive impact on earnings management.